CAPACITAÇÃO DOCENTE COMO FATOR DE QUALIDADE DO SETOR DE EDUCAÇÃO EM TURISMO. - Catramby, Teresa Cristina Viveiros (2004)
This research has the aims to present the tourism education situation, specifically the graduation, in the state of Rio de Janeiro. Capability is one of the most important issues for competitiveness in this field, it demands quality which must be a priority for private and public institutions that deal with tourism. The tourist product and the competences required for professional background are presented here in order to connect them to the needs of the tourist customer. This study investigates the hypothesis that the teacher s capability is one of the most influential points in professional quality. At this case study the professorship had been analyzed as one of the inputs of the educational process as well as pedagogical plan, technological structure and library. It was made a case study in colleges of Rio de Janeiro State (Brazil) with the purpose of analysing aspects involving curriculum and syllabus preparation, hiring professors, support to professors educational background and the disciplines that are important to future teachers and professors in their major in college. Through this case we were able to analyze the situation of the institutions, public and private, on concern of theirs professor, specifically the ones that graduate in tourism, at state of Rio de Janeiro. We have proved that quality of education is related to teachers capability and quality of theirs professorship and that has to be a priority for institutions that want to have quality. Key words: education, quality, tourism, and teaching.